Ser (e aprender a ser) negro e quilombola: processos de identificação étnica entre a escola e o quilombo, em Alto Alegre, Ceará - Silva, Miguel Ângelo Maia da (2019)
The present work deals with processes of ethnic identification, in reference to being black and quilombola, through an ethnography performed between the school and the quilombo, both located in the community of Alto Alegre, Queimadas district, rural area of Horizonte - CE. Its objective is to represent the constructive constructions in the Alto Alegre quilombo compared to the Pedro Eduardo Siqueira school. The school is a conservative institution, not only does it make sense to establish itself and is hierarchically related between individuals, but it also makes no political sense, to preserve what is always and does not. This is an ethnic community of the Alto Alegre community. Taking, initially, that ethnic groups are a type of social organization (BARTH, 2011), and that an ethnic identification refers to the use of a racial person, or for purposes of identification and mode, to relate to others.” (OLIVEIRA, 1976, p. 2), it starts from the idea that contemporary quilombola identities fall into acts of construction, and the educational question may represent the strategies of identity construction, in which the subjects react to an ecological element local, national and global over a history of adaptation by invention and selective constraints (BARTH, 2011). Then, inspired by Ezpeleta & Rockwell's (1989) studies of school as a “social construction”, and understanding that the heterogeneity and individuality of everyday life “necessarily impose the recognition of subjects who incorporate and objectify, in their own way, practices and pratiques”, which they appropriate in different moments and contexts of life ”(EZPELETA; ROCKWELL, 1989, p. 28), began to look at the culture that developed in the school, especially the one that unfolded in the classroom, and In discussing the strategies for conducting research, I decided that the study could not be limited to the school space alone. It took a holistic look beyond the school. And that meant being aware of everything that happened in the quilombola community of Alto Alegre, in the city of Horizonte, in the state of Ceará and in Brazil, and that has to do with the issues of identity in the school space in reference to a quilombola identity. Then, an ethnographic study was conducted in three social spaces for the transmission of education: the formal education space, the Pedro Eduardo Siqueira school and the training for Afro-Brazilian and African History and Culture teachers, which takes place at municipality of Horizonte; and the Alto Alegre quilombola community space, which brings together spaces for formal and informal education, such as NUPPIRH and the activities that take place at the Negro Cazuza Cultural Center.